The access to green spaces in public and private schools in Curridabat, Costa Rica - Castillo Echeverría, Carolina (2018)
This article exposes the results of a study that sought to compare public and private schools in the Curridabat canton to determine if  children have equal access to green spaces in their campuses and the effect it has on them to access these green spaces in their school. The research was carried out in two private and two public schools of the Curridabat canton, located in the province of San José, Costa Rica. It used a qualitative methodology based on observations of the school´s campuses, mapping and semi-structured interviews with school personnel and children between 7 and 12 years old. The results compare the external areas and green spaces of private and public schools and shows the importance it has for children to have access to these areas in schools.